Pengembangan Aplikasi Eventify: Sistem Web Terintegrasi antara Main App dan Admin Dashboard untuk Manajemen Event - Dwi Wahyuningtyas; Reihan Setya Banda Syah Putra; Raihan Canggih Panilih; Rahmat Nur Shidiq (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing prevalence of competitions and events necessitates efficient management systems to overcome challenges such as limited information dissemination and inefficient data handling. This study developed Eventify, an integrated web-based platform comprising a Main App for participants and organizers and an Admin Dashboard for monitoring and management. The system aims to simplify event administration, enhance transparency, and improve user experience. Built with the Laravel framework, Eventify utilizes a direct multi-database connection approach, streamlining data communication between the two applications. The development followed the SDLC waterfall model, encompassing analysis, design, implementation, and testing. Key findings indicate that Eventify effectively supports event creation, registration, participant data management, and administrative oversight. This integrated solution significantly improves operational efficiency and data transparency for event management.